2018
DOI: 10.1111/aas.13155
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cardiopulmonary resuscitation‐related injuries sustained during out‐of‐hospital cardiac arrests

Abstract: Older age, male gender, and public location were independently associated with CPR-related injuries. The duration of the resuscitation attempts did not affect the incident of injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Rev Assoc Med Bras 2022;68 (10): [1470][1471][1472][1473][1474][1475] Consistent with the literature [16][17][18] , our cases showed an abdominal injury rate of 4.8%, including liver pericapsular haematoma and pneumoperitoneum in 2 and 1 of 29 patients with thoracoabdominal injury associated with CPR.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Rev Assoc Med Bras 2022;68 (10): [1470][1471][1472][1473][1474][1475] Consistent with the literature [16][17][18] , our cases showed an abdominal injury rate of 4.8%, including liver pericapsular haematoma and pneumoperitoneum in 2 and 1 of 29 patients with thoracoabdominal injury associated with CPR.…”
Section: Discussionsupporting
confidence: 82%
“…The 2020 AHA and 2021 ERC guidelines limit the depth of each compression in CPR to 5-6 cm 2,4 . However, recent studies suggested that CPR may be associated with severe thoracoabdominal injuries [9][10][11] . Thoracic injuries due to chest compressions cause significant mortality and morbidity 6,7,12 .…”
Section: Discussionmentioning
confidence: 99%
“…Cardiopulmonary resuscitation can cause chest injuries— Table 3 [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. The incidence of injury is variable and can reach up to 100%, as demonstrated in a study by Jang SJ et al Differences in the number of injuries diagnosed may be related to the sensitivity of specific diagnostic tests.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of using a mechanical device during CPR is not clear. Studies by Smekal et al and Freiberg et al, comparing manual vs. mechanical chest compressions showed that rib fractures were more common after the use of a mechanical device [ 35 , 36 ]. In contrast, in the study by Kralij et al and Canakci et al, no significant difference was observed in terms of complications in patients who received mechanical compression compared to those who received only manual compression [ 29 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pathologist reported two such cases, but they were not considered as serious, which correspond with relevant literature. 17 The role of manual chest compressions (performed by lay people, first responders and ambulance crews) before mechanical chest compressions as potential cause of CPR related injuries, is difficult to document. We did not measure the actual force or chest properties (stiffness) in our study.…”
Section: Discussionmentioning
confidence: 99%